A novel modification of two-port laparoscopic ovarian cystectomy using a needlescopic instrument: One surgeon's initial experience - Satoshi Asai; Hitoshi Ishimoto; Akira Yabuno; Hironori Asada; Mikio Mikami; Yasunori Yoshimura (Wolters Kluwer Medknow Publications, 2016)
Background: Laparoendoscopic single-site surgery (LESS) is challenging even for an experienced laparoscopic surgeon. With the increasing application of LESS for ovarian cystectomy, there is an urgent need to improve and modify the surgical techniques. Method: We propose a modification of LESS with needlescopic surgery (LESS plus one puncture) as a way of improving the esthetic result and postoperative quality of life of the patient while causing less stress for the surgeon. Result: We retrospectively reviewed the medical records of the first 30 consecutive patients who underwent two-port surgery for teratoma resection. Conclusion: LESS plus one puncture for ovarian cystectomy appears as safe and feasible as conventional laparoscopic surgery and can allow for an almost "scarless" cosmetic result.